2020
DOI: 10.1097/sle.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Total Extraperitoneal Inguinal Hernia Repair Under Epidural Anesthesia Versus General Anesthesia

Abstract: Introduction: Laparoscopic total extraperitoneal (TEP) inguinal hernia repair is a well-known approach to inguinal hernia repair. The present study aims to compare the advantages and disadvantages of the TEP technique under general anesthesia (GA) and epidural anesthesia (EA). Materials and Methods: The patients were divided into 2 groups as those undergoing TEP under EA (Group 1) and those undergoing TEP under GA (Group 2). The 2 patient groups were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 21 publications
2
19
2
Order By: Relevance
“…8,23 In these 2 meta-analyses, surgery time was found to be longer for SA compared with the GA. In the clinical study of Sürek et al, 24 there was no difference between the EA and GA groups in terms of surgery time, while the total operative time was significantly longer in EA than in GA. In our study, operation times were compared and EA was found to be the longest (group GA: 55.2 ± 12.27 min, group SA: 55.1 ± 8.6 min, and group EA: 63.1 ± 10.18 min) (P < 0.001).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…8,23 In these 2 meta-analyses, surgery time was found to be longer for SA compared with the GA. In the clinical study of Sürek et al, 24 there was no difference between the EA and GA groups in terms of surgery time, while the total operative time was significantly longer in EA than in GA. In our study, operation times were compared and EA was found to be the longest (group GA: 55.2 ± 12.27 min, group SA: 55.1 ± 8.6 min, and group EA: 63.1 ± 10.18 min) (P < 0.001).…”
Section: Discussionmentioning
confidence: 83%
“…[33][34][35] There was no difference between SA and GA in terms of seroma and scrotal edema development in 2 meta-analysis studies. 7,8 Sürek et al 24 reported that there was no significant difference between the EA and GA groups in terms of seroma and scrotal edema development. In our study, similar to these studies and meta-analyses, no statistically significant difference was found between the GA, EA, and SA groups in terms of seroma and scrotal edema (P = 0.803 and 0.557).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were treated in a supine Trendelenburg’s position under general anesthesia or regional anesthesia. Epidural anesthesia and spinal anesthesia techniques were used for regional anesthesia 12,13…”
Section: Methodsmentioning
confidence: 99%